Case report: A case of rare metastasis of gastric cancer to the axillary lymph node metastasis treated with combination immunotherapy - Wang, Jin; Cheng, Yu; Wang, Yulin; Liu, Hengxin; Wu, Shuang; Tian, Guangwei; Qu, Jinglei; Qu, Xiujuan (Frontiers in Immunology, 2024)
Lymph node (LN) metastasis is a common mode of metastasis in advanced gastric cancer (GC), while axillary LN metastasis infrequently occurs in GC. There are few reports on this rare type of metastasis -especially its clinicopathological features -and systemic treatment are unclear. We describe a case of GC with extensive metastasis, including the rare axillary LN metastasis. The patient achieved partial response of optimal efficacy, who was treated with combination immunotherapy as second-line treatment for nearly two years. The potential mechanisms were revealed by clinical and immune characteristics, such as high expression of PD-L1, high tumor mutational burden (TMB-H), Epstein-Barr virus (EBV) positive and CD8 + tumor-infiltrating lymphocyte positive.